A melanin‐based trait is more strongly related to body size in the tropics than in temperate regions in the globally distributed barn owl family. (31st October 2018) - Roulin, Alexandre; Uva, Vera; Romano, Andrea
Abstract: Life history traits differ between organisms living in the tropics, Northern and Southern Hemispheres, and sexual selection is thought to be stronger close to the equator than in temperate regions. Although birds are often supposed to be more brightly coloured in the tropics, the current evidence of geographic variation in the intensity of sexual selection and sex‐specific natural selection is equivocal. Whether sex‐specific traits signal aspects of individual quality better in the tropics than in the temperate regions of the Northern and Southern Hemispheres therefore remains an open question. We examined predictions of this hypothesis in the Tytonidae family (barn owls and their relatives) because females, on average, display larger black spots on the tip of their ventral body feathers than males, and this trait is associated with aspects of individual quality. We measured the size of melanic spots and the wing length of 7893 Tytonidae skins collected worldwide and preserved in natural history museums. The covariation between spot size and wing length was stronger in females than in males, in large‐ than small‐spotted Tyto taxa and close to the equator than in temperate regions. This suggests that selection for spot size, which can be used by owls as an additional cue to assess individual body size and other aspects of phenotypic quality, is stronger in females than in males, particularly near the equator.